2019
DOI: 10.3389/fmicb.2019.00004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of Lactococcus lactis Indicates Niche Adaptation and Resolves Genotype/Phenotype Disparity

Abstract: Lactococcus lactis is one of the most important micro-organisms in the dairy industry for the fermentation of cheese and buttermilk. Besides the conversion of lactose to lactate it is responsible for product properties such as flavor and texture, which are determined by volatile metabolites, proteolytic activity and exopolysaccharide production. While the species Lactococcus lactis consists of the two subspecies lactis and cremoris their taxonomic position is confused by a group of strains that, despite of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 109 publications
(150 reference statements)
11
45
0
Order By: Relevance
“…To this regard, all 74 isolates of Streptococcus thermophilus from vegetable, fodder crop and flowering plant sources were able to produce EPS (Umamaheswari et al ., ). Additionally, although numerous strains of L. lactis contain chromosomal gene clusters for cell wall polysaccharide biosynthesis, only one gene cluster ( epsXABCDEFGHIJKL ) has been found exclusively in plant‐associated L. lactis isolates (Wels et al ., ).…”
Section: Characteristics Of Lab Relevant For Colonization Of Plant Sumentioning
confidence: 97%
See 1 more Smart Citation
“…To this regard, all 74 isolates of Streptococcus thermophilus from vegetable, fodder crop and flowering plant sources were able to produce EPS (Umamaheswari et al ., ). Additionally, although numerous strains of L. lactis contain chromosomal gene clusters for cell wall polysaccharide biosynthesis, only one gene cluster ( epsXABCDEFGHIJKL ) has been found exclusively in plant‐associated L. lactis isolates (Wels et al ., ).…”
Section: Characteristics Of Lab Relevant For Colonization Of Plant Sumentioning
confidence: 97%
“…heat shock proteins, chaperonins, USP proteins) as compared to when that strain was incubated in standard laboratory culture medium (Filannino et al ., ). Lastly, the analysis of whole genomes from 44 strains of L. lactis found that plant‐associated strains cluster separately from dairy‐associated strains (Wels et al ., ). Lactococcus lactis isolates from plants were found to have fewer amino acid requirements necessary for growth relative to L. lactis isolated from other sources (Ayad et al ., ).…”
Section: Characteristics Of Lab Relevant For Colonization Of Plant Sumentioning
confidence: 97%
“…As reported in the literature, the large metabolic capabilities of the lactis species, particularly in carbohydrate metabolism, may promote faster growth rate than the cremoris species (Kelleher et al, 2017). However, as lactose is the main carbohydrate in milk, this dairy environment is very well adapted to the cremoris species strains which have the necessary ability to break down this sugar (Wels et al, 2019). Moreover, several studies have shown that strains of the lactis species initially produce acid slowly (Herreros et al, 2003;Fusieger et al, 2020) and that, conversely, strains of the cremoris species usually produce better acidification than lactis species, both at the beginning and at the end of the fermentation (Nomura et al, 2006;Fernández et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of this new denomination is now well admitted. In the lactis group, both species are associated with well described growth characteristics (Wels et al, 2019). However, cremoris species have different phenotypes (Cavanagh et al, 2015a), with strains identified as "true" cremoris, and strains showing a Lactis phenotype (growth at 40 • C, in the presence of 4% NaCl and pH 9.2, and the ability to degrade arginine).…”
Section: Introductionmentioning
confidence: 99%
“…cremoris strains are also osmoresistant (27). Recent analyses using genotype-phenotype matching approaches with 43 L. lactis genomes have been unable to a identify specific gene(s), based on a presence/absence analysis, that is responsible for differences in osmoresistance between strains (28).…”
mentioning
confidence: 99%